Transcellular Passage of Neisseria meningitidis across a Polarized Respiratory Epithelium - Sutherland, Thomas C. (American Society for Microbiology (ASM), 2010)
Neisseria meningitidis is a major cause of sepsis and meningitis but is also a common commensal, present in the nasopharynx of between 8 and 20% of healthy individuals. During carriage, the bacterium is found on the surface of the nasopharyngeal epithelium and in deeper tissues, while to develop disease the meningococcus must spread across the respiratory epithelium and enter the systemic circulation. Therefore, investigating the pathways by which N. meningitidis crosses the epithelial barrier is relevant for understanding carriage and disease but has been hindered by the lack of appropriate models. Here, we have established a physiologically relevant model of the upper respiratory epithelial cell barrier to investigate the mechanisms responsible for traversal of N. meningitidis. Calu-3 human respiratory epithelial cells were grown on permeable cell culture membranes to form polarized monolayers of cells joined by tight junctions. We show that the meningococcus crosses the epithelial cell barrier by a transcellular route; traversal of the layer did not disrupt its integrity, and bacteria were detected within the cells of the monolayer. We demonstrate that successful traversal of the epithelial cell barrier by N. meningitidis requires expression of its type 4 pili (Tfp) and capsule and is dependent on the host cell microtubule network. The Calu-3 model should be suitable for dissecting the pathogenesis of infections caused by other respiratory pathogens, as well as the meningococcus.